Improving Vocabulary in Writing Recount Text at Grade VIII Students of SMP YP HKBP 1 Pematangsiantar Through Clustering Technique - Sihombing, Marino; Sitanggang, Loria; Sianipar, Inggrid; Herman, Herman (Pengabdian Masyarakat Sumber Daya Unggul, 2025)
This community service program aimed to improve students’ recount text writing skills by enhancing their mastery of past tense verbs through the application of clustering techniques within the Genre-Based Approach (GBA). The main problem addressed was the students’ limited ability to construct recount texts with appropriate structure, vocabulary, and chronological flow. The program involved socialization and training for 10 eighth-grade students at SMP YP HKBP 1 Pematangsiantar on May 13, 2025. The implementation methods included lectures, discussions, and writing practice, with evaluations conducted through observation, worksheet analysis, and student writing assessment. Results indicated that 80% of the participants showed significant improvement in text structure, use of past tense verbs, and idea organization. These findings suggest that the integration of clustering techniques and GBA is effective in enhancing students’ writing hardskills in the recount text genre.